2017
DOI: 10.21873/anticanres.11282
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of High-mobility Group Box-1 (HMGB1) and the Receptor for Advanced Glycation End-products (RAGE) in Cutaneous Malignancy: A Systematic Review

Abstract: Abstract. Inflammation and the immune system play a role in the development and progression of melanoma, basal cell carcinoma (BCC), and squamous cell carcinoma (SCC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…This result indicated that intracellularly formed AGE, rather than O‐GlcNAc modification, may further modify transcription factors including Hif1α and AP‐1, leading to the synergistic enhancement of MTM‐induced VEGF expression. Interestingly, VEGF was not induced by AGE, but its constitutive level was downregulated by Ager siRNA in PDL cells, implying that other agonistic ligands such as S100 and HMGB1 may also work for Ager in PDL cells . These suggestions may need to be further investigated and validated.…”
Section: Discussionmentioning
confidence: 97%
“…This result indicated that intracellularly formed AGE, rather than O‐GlcNAc modification, may further modify transcription factors including Hif1α and AP‐1, leading to the synergistic enhancement of MTM‐induced VEGF expression. Interestingly, VEGF was not induced by AGE, but its constitutive level was downregulated by Ager siRNA in PDL cells, implying that other agonistic ligands such as S100 and HMGB1 may also work for Ager in PDL cells . These suggestions may need to be further investigated and validated.…”
Section: Discussionmentioning
confidence: 97%
“…In the experimental setting, inhibition of HMGB1 release diminish ATP production and retard tumor growth [10]. Overexpression of HMGB1 in tumor tissue and increased HMGB1 serum level are near-universal in virtually every examined type of cancer, including colon carcinoma [11–13], hepatoma [14,15], breast cancer (BC) [16], pancreatic cancer [11], melanoma [17], ovarian cancer [18], and mesothelioma [19,20], indicating a carcinogenic role of HMGB1.…”
Section: Introductionmentioning
confidence: 99%
“…The use of decoys may not be restricted to S100A8/A9 since each receptor's extracellular region is capable of interacting with several ligands that are related to cancer progression. For example, RAGE interacts with AGEs, HMGB1 and most S100 family proteins; MCAM interacts with galectin‐3 and Wnt5a; and EMMPRIN interacts with cyclophilin A . Thus, interactions with these factors may provide additional decoy‐mediated suppressive effects.…”
Section: Resultsmentioning
confidence: 99%